Post-exercise Body Cooling: Skin Blood Flow, Venous Pooling, and Orthostatic Intolerance - Seeley, Afton D.; Giersch, Gabrielle E. W.; Charkoudian, Nisha (Frontiers in Sports and Active Living, 2021)
Athletes and certain occupations (e.g., military, firefighters) must navigate unique heat challenges as they perform physical tasks during prolonged heat stress, at times while wearing protective clothing that hinders heat dissipation. Such environments and activities elicit physiological adjustments that prioritize thermoregulatory skin perfusion at the expense of arterial blood pressure and may result in decreases in cerebral blood flow. High levels of skin blood flow combined with an upright body position augment venous pooling and transcapillary fluid shifts in the lower extremities. Combined with sweat-driven reductions in plasma volume, these cardiovascular alterations result in levels of cardiac output that do not meet requirements for brain blood flow, which can lead to orthostatic intolerance and occasionally syncope. Skin surface cooling countermeasures appear to be a promising means of improving orthostatic tolerance via autonomic mechanisms. Increases in transduction of sympathetic activity into vascular resistance, and an increased baroreflex set-point have been shown to be induced by surface cooling implemented after passive heating and other arterial pressure challenges. Considering the further contribution of exercise thermogenesis to orthostatic intolerance risk, our goal in this review is to provide an overview of post-exercise cooling strategies as they are capable of improving autonomic control of the circulation to optimize orthostatic tolerance. We aim to synthesize both basic and applied physiology knowledge available regarding real-world application of cooling strategies to reduce the likelihood of experiencing symptomatic orthostatic intolerance after exercise in the heat.